Africa and its "Chinese" debt at the time of COVID-19 - (:unkn) unknown (My University, 2020)
In a remarkable unanimity forced by an unprecedented health crisis, the IMF and the World Bank, the G20 and even Pope Francis have come out in favour of debt relief for the most indebted countries, at the forefront of which are many African countries, with China more or less in the dock. During a press conference in June 2020, Ma Zhaoxu, Vice Minister of Foreign Affairs, said that following the recommendations of the G20, China "had announced debt moratoria for 77 developing countries and territories". But what is the real burden of African debt to China, what does this debt mean and what is the role played by China and its companies?
Keywords: African Research